Efeito da gravidez na adolescência sobre os resultados perinatais em maternidades de nível terciário no ano de 2003 no estado do Ceará – Brasil - Cunha, Silvia de Melo (2005)
Study Objective: To check existence of association between mother’s age and newborn’s hospitalizing at Intensive Therapy Unit at tertiary level maternity on 2003 on Ceará – Brasil. To measure the variables birth weight and pregnancy age comparing groups by the mother’s age of precocious teenagers, late teenagers and adults. Method: transversal and descriptive study where it was rated the number of simple deliveries of alive newborns on Hospital Geral César Cals (HGCC) and Maternidade Escola Assis Chateaubriand (MEAC) since January 1s until December 31 on the year of 2003 and the 1351 simple deliveries newborn’s hospitalizing at Intensive Therapy Unit (ITU) of those hospitals were studied about mother’s age, pregnancy age and birth weight, through searches on books of maternity hospital, medical register and registers on electronics archives. Pearson’s chi-square, linear relation and Exact of Fisher tests were used on analysis of data. Chi-square test and odds ration (OR) with 95% confidence intervals (95%CI) were used to compare quantitative variables. Results: Eleven thousand four hundred twenty nine (11.429) women delivered at maternities hospitals studied, 24,8% were teenagers mothers , 11,8% newborns were hospitalized at ITU. Although there was indicative of linear relation, p= 0, 097 (<0,100), there wasn’t significant statically association between mother age and hospitalizing at ITU (p= 0,207). Was observe highest percentages of prematurely on newborns of precocious teenagers, (86,1%), when compared with late teenagers (85,2%) and adults. (74,8%), evidence that there was statically association between pregnancy age and mothers age (p< 0,001). However there wasn’t statically difference between precocious teenagers and late teenagers when prematurely was studied (OR 1,08; IC 95% 0,51 – 2,27). Although, there was statically difference when precocious and late teenagers were compared with adults. (OR 2.08; IC 1.05 - 4.13 e OR 1.93; IC 1.35 - 2.76). When birth weight was measured, there was highest percentages of low weight on children of precocious teenagers (87,5%) than late teenagers (83,0%) and adult (73,3%), evidence that there was significant statically association between birth weight and mothers age (p< 0,001). Statically there wasn’t difference of low weight between precocious and late teenagers (OR 1.42; IC 0.66 - 3.66). When precocious and late teenagers were compared with adults there was significant statically difference (OR 3.07; IC 1.50 – 6.25 e OR 2.15; IC 1.53 – 3.01 respectively). It was observed highest percentages of newborns with very low birth weight on precocious teenagers, but there wasn’t statically difference when they were compared with late teenagers, (OR 1.17; IC95% 0.69 – 1.97). When precocious and late teenagers were compared with adults there was significant statically difference (OR 1.65; IC95% 1.02 – 2.69 e OR 1.41; IC95% 1.07 – 1.86 respectively). Conclusions: It wasn’t found significant statically association between mother age and hospitalizing at ITU. There was significant statically association between pregnancy age and mother age and birth weight and mother age. There was significant statically difference between teenagers and adults about prematurely, low birth weight and very low birth weight percentages. The percentages of prematurely, low birth weight and very low birth weight were more frequent on precocious teenagers than late teenagers. However the odds ratio wasn’t significant statically.